2019
DOI: 10.18632/aging.102462
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced microRNA-10b-3p promotes esophageal squamous cell carcinoma growth and metastasis by targeting TSGA10

Abstract: Evidence has shown that hypoxia promotes esophageal squamous cell carcinoma (ESCC) growth and metastasis, but the molecular mechanisms underlying that response remain poorly understood. MicroRNAs (miRNAs) are post-transcriptional regulators that participate in various cancer-related processes. Here, we demonstrated that hypoxia along with hypoxia-inducible factor 1α significantly increased expression of miR-10b-3p. Inhibition of miR-10b-3p weakened the effects of hypoxia on ESCC cell proliferation, migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Hypoxia is a typical characteristic observed in the tumor microenvironment and drives the aggressiveness of many tumors, such as hepatocellular carcinoma (Kung-Chun Chiu et al, 2019), colorectal cancer (Qureshi-Baig et al, 2019), and esophageal squamous cell carcinoma (Zhang et al, 2019). Under hypoxic conditions, many transcription factors are activated in tumor cells, inducing various downstream signals regulating cell proliferation, motility, and apoptosis (Semenza, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia is a typical characteristic observed in the tumor microenvironment and drives the aggressiveness of many tumors, such as hepatocellular carcinoma (Kung-Chun Chiu et al, 2019), colorectal cancer (Qureshi-Baig et al, 2019), and esophageal squamous cell carcinoma (Zhang et al, 2019). Under hypoxic conditions, many transcription factors are activated in tumor cells, inducing various downstream signals regulating cell proliferation, motility, and apoptosis (Semenza, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It could be enriched in exosomes of hepatocellular carcinoma cells and was a potential marker for the diagnosis of early‐stage hepatocellular carcinoma 14 . Hypoxia could induce the expression of miR‐10b‐3p and promote the growth and metastasis of esophageal squamous cell carcinoma by targeting TSGA10 15 . It could also improve the invasion of PDAC through suppressed TIP30 and increased EGF 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that dysregulation of miR-NAs is common in cancer and that miRNAs can function as oncogenes or tumour suppressers [24][25][26][27][28]. Genomewide expression profiling of miRNAs using microarray analysis of tumour tissue and matched normal tissues has recognized hundreds of downregulated and upregulated miRNAs between two groups [29,30].…”
Section: Discussionmentioning
confidence: 99%